ANALISIS DAYA TAMPUNG BEBAN PENCEMAR SUNGAI PESANGGRAHAN (SEGMEN KOTA DEPOK) DENGAN MENGGUNAKAN MODEL NUMERIK DAN SPASIAL - Muhamad Komarudin; Sigid Hariyadi; Budi Kurniawan (Graduate School Bogor Agricultural University (SPs IPB), 2015)
The objective of the study is to calculate and analyze the pollution load capacity of the specified river segment using combination of the water quality model “QUAL2Kw” and Geographic Information System (SIG). Location of the study is Pesanggrahan river in the Depok City sections. The result of modeling shows that the actual pollutant load discharged to the river section for BOD, COD and TSS are 8.257; 59.930 dan 48.975 kg/days, respectively. Meanwhile the allowable pollutant load or the pollution load capacity of the section of the river for those pollutant parameters are 8.111, 58.20; 49.085 kg/days, respectively. It indicates that the pollution load capacity of the section of the river has been exceeded that needs reduction as much as load of 146 kg/days for BOD, 1,650 kg/days for COD and 110 kg/days for TSS in order to to meet the set water quality standard of the river section. The coefficient of determination (r2) of 0,99 for BOD and COD and 0,998 for TSS indicates that the modelled concentration of BOD, COD and TSS and those concentration of measured results show the strong relationship and the low value difference. In addition, the calibration of modeling results have an error rate of less than 10% indicated by the value of RMSE of 0.065, 0.09, 0.2 for BOD, COD and TSS, respectively. The error value shows that the water quality modeling results can be used for predicting the pollution load capacity or the allowable pollutant load of the river sectionKeywords: allowable pollutant load, GIS, Pesanggrahan River, pollution load capacity, QUAL2Kw